Pengaruh Kepatuhan Akad Jual Beli Salam dan Istishna’ terhadap Tingkat Perlindungan Konsumen (Hifz al-Mal) pada Transaksi Pre-Order (PO) di TikTok Shop - Julia Rachmawati; Dewi Riza Lisvi Vahlevi (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The use of TikTok Shop as a digital transaction platform is increasingly popular, particularly through the pre-order (PO) system offered to consumers. Although it provides convenience in shopping, the pre-order system also carries potential risks such as product uncertainty, delivery delays, and financial losses. From the perspective of Islamic economics, these conditions require compliance with Sharia-based contracts to ensure the protection of wealth (hifz al-mal). This study aims to analyze the effect of compliance with salam and istishna’ contracts on the level of consumer protection (hifz al-mal) in pre-order transactions on TikTok Shop. This study examines the contribution of salam and istishna’ contract compliance to the protection of consumer wealth (hifz al-mal) in the pre-order system on TikTok Shop. A quantitative approach was employed, with data collected from 169 respondents who had previously made purchases through the pre-order system. Data were analyzed using classical assumption tests and multiple linear regression with SPSS software to test the research hypotheses. The results indicate that compliance with salam and istishna’ contracts has a positive and significant effect on consumer protection, both partially and simultaneously. These findings confirm that adherence to Islamic principles is not merely normative but plays a crucial role in reducing financial risk and strengthening trust in digital transactions.